2005
DOI: 10.1242/jcs.02605
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial fluid flow induces myofibroblast differentiation and collagen alignment in vitro

Abstract: The differentiation of fibroblasts to contractile myofibroblasts, which is characterized by de novo expression of α-smooth muscle actin (α-SMA), is crucial for wound healing and a hallmark of tissue scarring and fibrosis. These processes often follow inflammatory events, particularly in soft tissues such as skin, lung and liver. Although inflammatory cells and damaged epithelium can release transforming growth factor β1 (TGF-β1), which largely mediates myofibroblast differentiation, the biophysical environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
284
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 335 publications
(309 citation statements)
references
References 64 publications
21
284
1
3
Order By: Relevance
“…29 The effect of interstitial collagen accumulation on water flow has been demonstrated in vitro both in normal interstitia from various organs 29 and in conditions of fibrosis. 30 Reduced osmotic conductance by the fractional volume occupied by collagen fibrils results from three mechanisms: (1) exclusion of glycosaminoglycans from the intrafibrillar space, thereby increasing their extrafibrillar concentration; (2) reduction of the mean hydraulic radius in the interstitium, leading to a reduced area for flow; and (3) tortuosity, which increases the path length for flow. 29 Our results show that increased collagen deposition and concentration in the peritoneal interstitium restricts water transport in vivo, leading to UF failure and loss of free-water transport in patients with EPS.…”
Section: Discussionmentioning
confidence: 99%
“…29 The effect of interstitial collagen accumulation on water flow has been demonstrated in vitro both in normal interstitia from various organs 29 and in conditions of fibrosis. 30 Reduced osmotic conductance by the fractional volume occupied by collagen fibrils results from three mechanisms: (1) exclusion of glycosaminoglycans from the intrafibrillar space, thereby increasing their extrafibrillar concentration; (2) reduction of the mean hydraulic radius in the interstitium, leading to a reduced area for flow; and (3) tortuosity, which increases the path length for flow. 29 Our results show that increased collagen deposition and concentration in the peritoneal interstitium restricts water transport in vivo, leading to UF failure and loss of free-water transport in patients with EPS.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-C also induces TGFb secretion by LECs (J. Munson and M. Swartz, unpublished data), which can promote regulatory T-cell education and drives fibroblast-to-myofibroblast transformation and stromal stiffening. Finally, increased interstitial flow in the tumor stroma due to high pressure gradients at the tumor margin also promotes TGFb activation, myofibroblast transformation, and stromal stiffening (44), and promote fibroblast-led tumor-cell invasion (45). Drawings are courtesy of Katie Hubbell, University College London, UK.…”
Section: Lymph Flow Of Antigensmentioning
confidence: 99%
“…It was found in rats that interstitial fluid flow induces collagen alignment. 15 In other studies, interstitial fluid channels formed before lymphatic endothelial cell organization and could direct lymphangiogenesis. 16 Uzarski et al found that interstitial fluid and edema resolution readily occur across the scar-free regenerating skin in the absence of VEGFR-3 signaling and lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 90%